2018
DOI: 10.1186/s13287-018-0906-1
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells and porous β-tricalcium phosphate composites prepared through stem cell screen-enrich-combine(−biomaterials) circulating system for the repair of critical size bone defects in goat tibia

Abstract: BackgroundEfficacious bone substitute is essential for the treatment of a critical size bone defect. Currently, the bone substitutes commonly used in clinical practice lack osteogenic capacity and the therapeutic efficacy is not ideal. Herein, a novel stem cell screen-enrich-combine(−biomaterials) circulating system (SECCS) was introduced to provide the substitutes with osteogenic ability. The stem cell screening, enrichment, and recombination with substitutes could be integrated during the surgical operation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…Until now, no reliable conclusion was found to explain the greater retaining of MSCs to carrier materials compared to other nuclear cells. Chu et al (2018) showed that filtration of bone marrow cells through various BSMs led to an enrichment of MSCs and their direct adhesion to the surfaces of porous BSM [53]. Importantly, the filtration enrichment method allows MSC concentration without interference from exogen agents, revealing no significant changes in phenotypic characteristics of the MSCs, osteogenetic fate, specific antigens, gene expression profile, cell cycle stage and apoptosis rate compared to before filtration [37,44].…”
Section: Conditioning Systems Composites and Growth Factorsmentioning
confidence: 99%
“…Until now, no reliable conclusion was found to explain the greater retaining of MSCs to carrier materials compared to other nuclear cells. Chu et al (2018) showed that filtration of bone marrow cells through various BSMs led to an enrichment of MSCs and their direct adhesion to the surfaces of porous BSM [53]. Importantly, the filtration enrichment method allows MSC concentration without interference from exogen agents, revealing no significant changes in phenotypic characteristics of the MSCs, osteogenetic fate, specific antigens, gene expression profile, cell cycle stage and apoptosis rate compared to before filtration [37,44].…”
Section: Conditioning Systems Composites and Growth Factorsmentioning
confidence: 99%
“…The benefits of MSC therapy are mainly attributed to paracrine effects via soluble factors, exerting both immunoregulatory and regenerative actions [11]. Although implanted MSC may act as osteoprogenitors [12][13][14], most evidence indicates that newly formed bone is mainly derived from host progenitors. The mechanisms by which macrophages contribute to MSC-mediated tissue repair remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The SECCS we developed previously can rapidly incorporate processes of screening, enrichment of autologous bone marrow MSCs and generation of composites with porous bone substitutes intraoperatively. These composites have shown superior osteogenic effects in animal models and clinical patients [10,25]. In this study, the number of MSCs in bone marrow was signi cantly decreased after treatment with SECCS, indicating that MSCs successfully adhered to the porous β-TCP.…”
Section: Discussionmentioning
confidence: 52%
“…Preparation and characterisation of MSCs/β-TCP The mixture of MSCs/β-TCP was prepared by SECCS, as previously reported [10]. Brie y, after the goat was fully anaesthetised, approximately 55 ml of bone marrow was taken from the bilateral anterior superior iliac spines.…”
Section: Fabrication Of Ti6al4v Frame and Rounding Of Its Distal Surfacementioning
confidence: 99%
See 1 more Smart Citation